Research on Productive Performance and Quality of Milk Obtained from Simmnetal Cows Grown in Agricultural Conditions of Rupea, Brasov County - Eugen Claudiu Jurco; Grigore Onaciu; Zamfir Marchis (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies, 2016)
The study focussed on the Romanian spotted breed-Simmental type was aimed to evaluating the productive potential and some reproductive indices in the period 2013-2015 in Sona farm from Brasov county. The main indicators taken into consideration to analyze the whole herd were the following: milk yield, milk quality, age of first calving, mammary repose and calving interval. Analyzing milk production, this was increasing from 5439 kg in 2013 to 7400 kg in 2015, with an average for the entire period of 6324.33 kg with 4.23% fat and 3.42% protein. Also the fat and protein content have increased over this period, from 4.13 % for fat and 3.25 % for protein in 2013, to 4.34 % and 3.56 respectively in 2015. Analyzing the main indicators of reproduction for a period of three years it was found that calving interval is on average of 401 days and mammary repose is around of 54 days. It is clearly observed that during this period the production is increasing, this shows that cows from the Sona farm records genetic progress regarding qualitative and quantitative milk production. The research has done much to show the productive potential and popularity of the Romanian spotted breed-Simmental type in Transylvania region.